Attack on crypsis: Molecular and morphological study of Dendrodoris Ehrenberg, 1831 (Mollusca: Gastropoda: Nudibranchia) from the Mediterranean Sea and Northern Atlantic Ocean reinstates Dendrodoris temarana Pruvot-Fol, 1953 - Galià-Camps, Carles; Cervera, Juan Lucas; Valdés, Ángel; Ballesteros, Manuel (Zootaxa, 2022)
The genus Dendrodoris is ascribed to the family Dendrodorididae, whose members are characterized lacking spicules in the dorsum as well as a radula, one of the most important taxonomic traits to distinguish and define nudibranch species. The absence of this taxonomic character makes difficult to delineate species based on morphologic traits, and consequently, several cryptic species may remain unreported resulting in a potential underestimation of the real diversity of the genus. Species delimitation analyses based on molecular data constitute an important tool to unveil cryptic species, especially when morphology may be misleading. However, for the genus Dendrodoris, only two molecular studies have been performed to date, both based on Indo-pacific species and the molecular marker COI. In the present study, we performed a multilocus approach using the molecular markers COI, 16S and H3 based on 47 Dendrodoris specimens from the North Atlantic Ocean and Mediterranean Sea. As a result, we detected monophyly for five of the previously accepted species plus the presence of an unidentified one. Using morphological and anatomical data from 14 additional individuals and a review of the literature, we verified this unidentified species is the previously synonymized species Dendrodoris temarana Pruvot-Fol, 1953, and we redescribe it morphologically (chromatic pattern, gills, rhinophores and anal papilla), anatomically (neural, circulatory, digestive and reproductive systems), and biologically herein. D. temarana is differentiated by its chromatic pattern, previously thought to be intraspecific variation of D. grandiflora (Rapp, 1827), D. limbata (Cuvier, 1804) and D. herytra Valdés & Ortea in Valdés, Ortea, Avila & Ballesteros, 1996, and therefore it is considered a pseudocryptic species. This study increases the number of valid species in the North Atlantic and Mediterranean to nine and confirms the importance of integrative taxonomic approaches to resolve the identification of cryptic species in complex groups.